Parameters of the signal being received at the low level part of the RAS bistatic systems path - Панченко, А.Ю. (Radiotekhnika, 2012)
Electromagnetic waves diffraction on air dielectric permeability nonuniformities at acoustic wave packet passage is analyzed. The approximation methods needed for presentation of rather cumbersome expression of the signal being received in the form possible for numerical calculations is offered. The directed properties of the wave beam are taken into consideration. Physical factors of interaction are considered, the numerical model is created and the algorithm for calculation of intensity and Doppler shift of the received signal frequency in the RAS system bistatic zone with the aperture antennas is described. Physical results of simulation are analyzed taking into account the available experimental data, the model precision and the ways of its perfection re estimated.